Popular misconceptions of entrepreneurship education in a higher education institution in Nigeria - Olele, Clara; Uche, Chineze (South African Journal of Higher Education, 2016)
The study investigated the levels of misconceptions of entrepreneurship education among students, ascertained the extent to which students who offered entrepreneurship education have entrepreneurial mindset, identified the teaching strategies mostly used for teaching entrepreneurship education, and analyzed the contents in entrepreneurship curriculum. A structured questionnaire was used to collect data from 150 randomly sampled students in 2 faculties in the University of Port Harcourt, in Niger Delta region of Nigeria. Frequencies, percentages, mean scores and z-test were the statistical tools used for analyzing the data. The findings identified six major misconceptions about entrepreneurship education among students; it established that the strategies used for teaching/learning entrepreneurship education were not experiential and activity –oriented to enhance active participation of students, and that the focus of the curriculum content were basically on entrepreneurship learning skills only, although the students have entrepreneurship mindset. The following recommendations were made: University authorities should collaborate with entrepreneurial experts, curriculum experts, educational technologists, policy-makers and politicians, to form a forum and re-design entrepreneurship education curriculum, paying attention to contents, activities, delivering strategies, and personality development, among others. Key words- unemployment, entrepreneurship, entrepreneurship mindset, mindset, social entrepreneurs, generic skills